Darwinizing culture - Aunger, Robert (Oxford University Press, 2000)
This book pits leading intellectuals, (both supporters and opponents of meme theory), against each other to battle it out, and state their case. With a forward by Daniel Dennett, and contributions form Dan Sperber, David Hll, Robert Boyd, Susan Blackmore, Henry Plotkin, and others, the result is a thrilling and challenging debate that will perhaps mark a turning point for the field, and for future research. Superbly edited by Robert Aunger, this is a thought provoking book that will fascinate, stimulate, (and occasionally perhaps infuriate) a broad range of readers including psychologists, biologists, philosophers, linguists, and anthropologists